In Vitro Screening of two Flavonoid Compounds Isolated from Cassia alata L. Leaves for Fungicidal Activities - Rahman, MS; Ali, MY; Ali, MU (Journal of Bio-Science, 2009)
Key words: Cassia alata, flavonoids, fungicidal activities. DOI:10.3329/jbs.v16i0.3759 J. bio-sci. 16: 139-142, 2008